Explaining political attention allocation with the help of issue character: evidence from the European Council. Issue 3 (24th March 2015) - Alexandrova, Petya
Abstract : Policy issues compete for the attention of political actors, and the size of the agenda an issue can occupy is largely determined by the way in which it is defined. This logic constitutes a simple agenda-setting model in which factors related to the participants in the policy process and their context influence the attention a single issue receives after being problematised. In order to be able to apply this model to the construction of a whole agenda, we need to add an intermediate step. This study proposes to do so by incorporating the notion of issue character and offers an empirical application of the adapted model to the European Council, a crucial informal player in European Union (EU) agenda setting. Using a dimensionality reduction technique, the composition of the agenda is broken down to two constitutive dimensions – core vs. non-core themes of government and economic vs. non-economic character. Since the first structuring element is in line with existing knowledge and the role expectations for the European Council, the analysis concentrates on the second type. Changing saliency levels of the economic issue character of the agenda are used as a dependent variable in a model, including predictors related to the nature of the institution and contextual factors. The results show that leftist European Council party ideology and growing government deficit in the EU contribute to the increasing prominence of the economic dimension, which in turn explains rising levels in attention to various issues, especially of the non-core themes type.